PENGGUNAAN PERMAINAN KARTU TRUTH OR DARE PADA MATERI NILAI-NILAI PANCASILA UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS IV SD NEGERI KUTA PASIE KABUPATEN ACEH BESAR - Sukma; Mislinawati; Nurmasyitah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve students’ understanding of Pancasila values through the use of the Truth or Dare card game in fourth-grade students at SD Negeri Kuta Pasie, Aceh Besar Regency. This research employed a qualitative approach with Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 23 students. Data collection techniques included observation of teacher and student activities as well as learning outcome tests. The results showed that the use of the Truth or Dare card game improved both student activity and understanding. In the first cycle, the average student score was 68.69 with a learning mastery percentage of 60.87%, categorized as sufficient. After improvements in the second cycle, there was a significant increase in both learning activities and student outcomes, reaching the predetermined success indicators. In addition, teacher activity was categorized as very good, while student activity improved from good to very good. Therefore, the Truth or Dare card game is proven to be effective in enhancing students’ understanding of Pancasila values and creating a more active, interactive, and enjoyable learning environment.